An improved imaging algorithm for spaceborne MAPs sliding spotlight SAR with high-resolution wide-swath capability - Kuang, Hui; Chen, Jie; Yang, Wei; Liu, Wei (Chinese journal of aeronautics, 2015)
Conventional synthetic aperture radar（SAR） systems cannot achieve both highresolution and wide-swath imaging simultaneously.This problem can be mitigated by employing multiple-azimuth-phases（MAPs） technology for spaceborne sliding spotlight SAR systems.However, traditional imaging algorithms have met challenges to process the data accurately, due to range model error, MAPs data reconstruction problem, high-order cross-coupling phase error and variation of Doppler parameters along the azimuth direction.Therefore, an improved imaging algorithm is proposed for solving the above problems.Firstly, a modified hyperbolic range equation（MHRE） is proposed by introducing a cubic term into the traditional hyperbolic range equation（THRE）.And two curved orbit correction methods are derived based on the proposed range model.Then, a MAPs sliding spotlight data reconstruction method is introduced, which solves the spectral aliasing problem by a de-rotation operation.Finally, high-order cross-coupling phases and variation of Doppler parameters are analyzed and the corresponding compensation methods are proposed.Simulation results for point-target scene are provided to verify the effectiveness of the proposed algorithm.